Platformisation and human rights - Nardoni, Maruška (Teorija in praksa, 2021)
The article aims to explore the public's fear of data being misused when using European Covid-19 contact-tracing applications. The point of departure lies in considering the research question of whether the Covid-19 pandemic has influenced the platformisation of traditional institutions, i.e., whether the design of Europe's proximity-tracing applications mimic the data intensive web services of commercial platforms, namely commercial APIs and their data policies, in order to bypass the right to privacy. We accordingly argue that is vital to address the public's fears of governmental and corporate dataveillance as well as data misuse while using such apps. The investigation entails of a critical analysis of the Exposure Notification System framework designed by Apple and Google (or GAEN) and the OstaniZdrav application. The article rejects the justification of the public's fear of governmental dataveillance, while recognising the possibility of corporate data misuse.
Keywords: Covid-19; Data abuse; Epidemics; Epidemije; Metadata; Metapodatki; Mobile apps; Mobilne aplikacije; Pravica do zasebnosti; Right of privacy; Zloraba podatkov